Voluntary carbon markets: A critical assessment - Leonhard Meitner (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
The looming climate crisis calls for the development of novel forms of response, but so far, climate change action does not meet its ambitions to tackle the issue. Voluntary Carbon Markets (VCMs) are one proposed solution to bridge the gap. However, VCMs are criticized for not providing real climate benefits and exacerbating inequality. This paper critically assesses VCMs, focusing on their regulatory, ecological, and social dysfunctions through an ecological economics lens. It identifies key issues such as inadequate transparency, compromised environmental integrity due to issues of additionality, permanence, double counting, carbon leakage, rebound effects, and adverse social impacts. By analyzing these dysfunctions and the underlying theoretical assumptions, the paper highlights how power relations, fundamental uncertainties, information asymmetries, and the commodification of nature contribute to the observed problems in VCMs. Through a qualitative literature analysis, this research provides a comprehensive evaluation of VCMs' role in global climate policy, emphasizing the need for robust regulatory frameworks, transparency, and inclusive decision-making processes to enhance their efficacy. The findings suggest that while VCMs have potential, addressing their inherent limitations is crucial for their legitimacy and effectiveness in combating climate change.
Keywords: F64; Q50; Q54; Q57; Q58; 330; Voluntary carbon markets; carbon offsetting; regulatory frameworks; ecological economics; environmental integrity